"VARNA" FOLKLORE ENSEMBLE – ESTABLISHMENT AND CONTINUITY - Galev, Dilyan (E-Journal VFU, 2025)
The present article examines the history, structure, and significance of the "Varna" Folklore Ensemble as a sustainable cultural institution that preserves and develops its activities within the context of folk stage art. A retrospective of the ensemble's development from its establishment in 1960 to the present day is presented, with a focus on its contribution in a national context. The article analyzes the ensemble's role as a bridge between generations, an educational environment, and a research platform within amateur art.
Keywords: dance school; folk ensemble; choreographer; artistic director; dance group